2019
DOI: 10.1002/pip.3230
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of p‐type silicon heterojunction solar cells fabricated using commercial‐grade low‐lifetime silicon wafers

Abstract: In this work, we integrate defect engineering methods of gettering and hydrogenation into silicon heterojunction solar cells fabricated using low-lifetime commercial-grade p-type Czochralski-grown monocrystalline and high-performance multicrystalline wafers. We independently assess the impact of gettering on the removal of bulk impurities such as iron as well as the impact of hydrogenation on the passivation of grain boundaries and B-O defects. Furthermore, we report for the first time the susceptibility of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…The photovoltaic market is rapidly growing [1] and the crystalline silicon (c-Si) technology dominates the market [2]. As large-area industrial efficiencies have recently overcome the 24% mark [3] with passivated emitter rear cell (PERC) architecture and the 25% mark [4,5] with silicon heterojunction (SHJ) architecture, there is a demand for novel concepts and materials aimed at increasing further the power conversion efficiency. The SHJ architecture combines the advantages of thin-film silicon technology with a c-Si absorber to selectively collect the generated carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The photovoltaic market is rapidly growing [1] and the crystalline silicon (c-Si) technology dominates the market [2]. As large-area industrial efficiencies have recently overcome the 24% mark [3] with passivated emitter rear cell (PERC) architecture and the 25% mark [4,5] with silicon heterojunction (SHJ) architecture, there is a demand for novel concepts and materials aimed at increasing further the power conversion efficiency. The SHJ architecture combines the advantages of thin-film silicon technology with a c-Si absorber to selectively collect the generated carriers.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that with the addition of a dedicated gettering step to improve material quality, Descoeudres et al observed an efficiency gain of %0.2% abs in batches of p-type SHJ solar cells. [10] In previous studies, we have also demonstrated the role of gettering in increasing the lifetime of p-type Cz silicon, [5,11,12] which translated to a %1% abs increase in the efficiency of SHJ solar cells. These results together indicate the need for gettering as a defect-engineering process to enhance the quality of p-type silicon wafers for SHJ solar cells applications.…”
mentioning
confidence: 83%
“…However, to date, little work has been done investigating LID in p-type SHJ solar cells. [11,20] For example, LID testing was not performed for the record cells from Descoeudres et al, although it was noted such wafers are likely to suffer from bulk degradation due to light-induced effects, [10] albeit with presumably a reduced total defect concentration due to the high wafer resistivity (6 Ω cm after gettering and the annihilation of thermal donors). In our recent work, we fabricated p-type SHJ solar cells that were susceptible to an efficiency degradation of 0.9% abs (4.7% rel ); [20] however, the degradation could be greatly reduced to 0.2% abs (1% rel ) using an advanced hydrogenation process.…”
mentioning
confidence: 99%
See 2 more Smart Citations